The mechanism of NLRP3 inflammasome activation and its pharmacological inhibitors - Zhan, Xiaoyan; Li, Qiang; Xu, Guang; Xiao, Xiaohe; Bai, Zhaofang (Frontiers in Immunology, 2023)
NLRP3 (NOD-, LRR- and pyrin domain-containing protein 3) is a cytosolic pattern recognition receptor (PRR) that recognizes multiple pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs). Once activated, NLRP3 initiates the inflammasome assembly together with the adaptor ASC and the effector caspase-1, leading to caspase-1 activation and subsequent cleavage of IL-1β and IL-18. Aberrant NLRP3 inflammasome activation is linked with the pathogenesis of multiple inflammatory diseases, such as cryopyrinassociated periodic syndromes, type 2 diabetes, nonalcoholic steatohepatitis, gout and neurodegenerative diseases. Thus, NLRP3 is an important therapeutic target, and researchers are putting a lot of effort into developing its inhibitors. The review summarizes the latest advances in the mechanism of NLRP3 inflammasome activation and its pharmacological inhibitors.